Cellular Energy Metabolism in T-Lymphocytes. (2nd January 2015) - Gaber, Timo; Strehl, Cindy; Sawitzki, Birgit; Hoff, Paula; Buttgereit, Frank
<x xml:space="preserve">Abstract</x> Energy homeostasis is a hallmark of cell survival and maintenance of cell function. Here we focus on the impact of cellular energy metabolism on T-lymphocyte differentiation, activation, and function in health and disease. We describe the role of transcriptional and posttranscriptional regulation of lymphocyte metabolism on immune functions of T cells. We also summarize the current knowledge about T-lymphocyte adaptations to inflammation and hypoxia, and the impact on T-cell behavior of pathophysiological hypoxia (as found in tumor tissue, chronically inflamed joints in rheumatoid arthritis and during bone regeneration). A better understanding of the underlying mechanisms that control immune cell metabolism and immune response may provide therapeutic opportunities to alter the immune response under conditions of either immunosuppression or inflammation, potentially targeting infections, vaccine response, tumor surveillance, autoimmunity, and inflammatory disorders.